THE IMPLEMENTATION OF SPIRITUAL COMPANY IN IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN TAMAN BATIK TERANG BULAN GROUP YOGYAKARTA - Reza Widhar Pahlevi (Program Studi Manajemen, 2018)
Good Corporate Governance is very closely discussed with spirituality that is based on religious teachings. Companies that pay attention to the spiritual aspects of doing business can be developed into a sustainable company. Companies that pay attention to the spiritual aspects of running a business, can develop into a sustainable company. Companies that are included in the category of spiritual companies make Good Corporate Governance (GCG) as a guideline and company value (company value) which is always upheld and practiced in daily business activities. This study aims to describe the implementation of spiritual company on the principles of good corporate governance in the Taman Batik Terang Bulan Group in Yogyakarta. The method used to determine informants is purposive sampling. In this qualitative research data collection using interviews, documentation and observation. From the results of this study, it can be concluded that the implementation of the principles of good corporate governance in the Taman Batik Terang Bulan is quite good. This is proven by spiritual values in business activities. However, there is a need to improve understanding of the financial system and basic terms in financial accounting and the need for clear standards from companies in financial records and companies must be able to internalize and synergize basic GCG guidelines such as transparency, responsibility, accountability, independence, and fairness to stakeholders.